Ultra-thin carbon nanosheets-assembled 3D hierarchically porous carbon for high performance zinc-air batteries. (November 2019) - Chen, Yu; Kone, Issa; Gong, Yi; Xie, Ao; Hu, Hanjun; Kong, Dandan; Liu, Jia; Tang, Yang; Yang, Xiaojin; Pang, Ran; Wan, Pingyu
Abstract: The oxygen reduction/evolution reactions play a paramount role in determining the performance of rechargeable metal-air batteries and fuel cells. Herein, we have successfully synthesized FeN-doped hierarchically porous carbon (FeN-HPC) materials with 3D honeycomb-like structure by NaCl-assisted pyrolysis method, which uses green and cheap glucose and dicyandiamide as organic precursors. Due to the extremely high percentage (93.7%) of graphitic-N & pyridinic-N in ultra-thin carbon nanosheets-assembled hierarchical structure with macro-meso-micro pores and large specific surface area, FeN-HPC exhibits excellent ORR activity, which surpasses commercial Pt/C manifested in higher half-wave potential (0.888 V vs. 0.845 V) and kinetic current density (23.2 mA cm −2 vs. 3.6 mA cm −2 @0.85 V). The primary zinc-air battery using FeN-HPC electrocatalyst exhibits a peak power density of 241 mW cm −2 at a high current density of 344 mA cm −2 . Moreover, after coupling with non-precious NiFe-hydroxides nanosheets, the rechargeable Zn-air battery exhibits a narrow potential gap of 0.61 V between charging and discharging. Significantly, the battery exhibits excellent durability with a negligible decrease (0.76%) of discharging potential after 1000 cycles, demonstrating significantly better performance than that of Zn-air batteries previously reported. Our work provides a promising way for building highly efficient electrocatalyst and high performance rechargeable zinc-air batteries. Graphical abstract: Image 1